Os princípios da legalidade e da segurança jurídica e o Parágrafo Único do Artigo 116 do Código Tributário Nacional - Quintella, Caio Cesar Nader (2014)
Complementary Law No. 104/2001 inserted the sole paragraph to Article 116 of the National Tax Code. Since such a provision was inserted in Chapter III of the Tax Codex, which deals with the triggering event and, specifically, in Article 116, for the regulation of the time of its occurrence, we would be facing a general rule that would affect the observation of occurrence of such a legal phenomenon. Given this legislative innovation of general application in the legal and tax relations, initially we analyze the interaction with the other elements that make up the national legal system, and verify its formal and material adequacy. Particularly given the immense thematic relevance of the topic and its regency in Tax Law as subsystem, we analyze the Principle of Legality, its scope and developments, to foster the engagement of provisions and effects brought with the insertion of the sole paragraph to Article 116 of the National Tax Code. Also, by the very result of such an analysis, we started to check the content, scope and consequences of the principle of legal certainty, which has an unquestionably great level abstraction and penetration into the national legal system in order to confront its corollary and impositions with the legal content and consequences of the instrument under investigation. Likewise, we address the institutes and subjects related to the central object of study, giving a greater depth to reflect on their compliance with the principles analyzed and on other general rules governing the Tax Law in Brazil. At the end, before all observations made on the subject, we promote the proper completion of the study